REPRESENTASI NASIONALISME DALAM FILM BATTLE OF SURABAYA - Fajar Ardi; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesian nationalism is now a nationalist stance in the independence is no longer the attitude of nationalism and anti-colonialism. The values of nationalism today are conveyed through the medium of film, because the film is a cinematographic work which can serve as a means of cultural education or cultural education. This study uses qualitative research methods to the analysis of semiotics John Fiske. The subjects were movie Battle Of Surabaya. Data obtained by the method of observation and documentation. Unit data analysis were selected based on a scene that has a sign of nationalism as much as 15 scene. Mechanical examination of the validity of data using using triangulation. The results of this study indicate the representation of nationalism in the film Battle Of Surabaya there is a message, meaning and values of nationalism for the Indonesian people, especially for the younger generation of Indonesia. Message and meaning of nationalism among others is the love of the people of Indonesia, Solidarity humanity as a nation of culture of mutual respect and cooperation between the people of Indonesia, willing bekorban have loyalty to the nation and the State by paying attention to the public interest .. This film can be used as a lesson for us to be able to interpret more nationalism is needed this nation. Keyword: representation, nationalism, film Battle of Surabaya.